Permanent education in the practice of preceptorship in primary health care (Research, Society and Development, 2020)
Aims: to describe the activities of nurse preceptors in the primary care environment and their role in the training of nursing students; to identify the competencies that those preceptors must develop and to analyze the strategies that lead to the development of such competencies. Method: this is a descriptive-exploratory study using a qualitative approach. Participants include eleven nurse preceptors. This research has been approved by the IRB of the City of Rio de Janeiro, under protocol no. 69A/2013; and also by IRB of Antonio Pedro University Hospital, under protocol no. 31643/2012. CAAE 02519512.0.0000.5243. Results: have been divided into two categories very relevant: the role of the nurse preceptor in the training of nursing students and the challenges faced by the nurse preceptor in the primary care environment in terms of the needs and competencies required on the part of the nurse preceptor.  Conclusion: the need for a more proactive approach on the part of preceptors concerning their own practice. This results in a lack of planning skills on the part of the nurse preceptors when it comes to engaging in an efficient teaching-learning process.